2008
DOI: 10.1063/1.2971192
|View full text |Cite
|
Sign up to set email alerts
|

Plasmonic properties of a metallic torus

Abstract: Using the plasmon hybridization method, we investigate the optical properties of metallic tori of different shapes and for different polarizations. The plasmon energies are found to be strongly dependent on polarization and on the aspect ratio of the torus, which we define as the ratio of the radii of the two circles that define the structure. For incident light polarized in the plane of the torus, the optical spectrum is characterized by two features, a long wavelength highly tunable dipolar plasmon resonance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
38
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 48 publications
0
38
0
Order By: Relevance
“…First, it has been shown that the wavelength λ 0 of the ring plasmonic resonance can be tuned by geometry across the visible and near-infrared spectral range [29][30][31][32]. Second, a certain degree of field enhancement is expected in split rings and closely spaced rings, and its effect on the LSPR sensitivity can be investigated.…”
Section: Numerical Results For the Lspr Sensitivitymentioning
confidence: 99%
See 1 more Smart Citation
“…First, it has been shown that the wavelength λ 0 of the ring plasmonic resonance can be tuned by geometry across the visible and near-infrared spectral range [29][30][31][32]. Second, a certain degree of field enhancement is expected in split rings and closely spaced rings, and its effect on the LSPR sensitivity can be investigated.…”
Section: Numerical Results For the Lspr Sensitivitymentioning
confidence: 99%
“…Markedly, nearly all of the literature focuses upon discovering a nanofeature geometry that enhances the LSPR sensitivity (e.g., spheres [10][11][12], rods [13][14][15][16][17][18], shells [19][20][21][22][23][24][25], disks [26][27][28], rings [29][30][31][32], and crescents [33][34][35]). However, several groups have concentrated on analytical estimation of LSPR sensitivity regardless of nanoparticle geometry.…”
Section: Introductionmentioning
confidence: 99%
“…[48][49][50][51] Fig. 1(c) and (d) compare σ sca and σ ext of the torus when the silver layer in the multifilm is optically thick (t = 30 nm) or thin (t = 3.4 nm).…”
mentioning
confidence: 97%
“…While for perpendicular polarization, the spectrum exhibits a single feature made up of several closely spaced higher order torus modes which are only weakly dependent on the aspect ratio [67]. Also, the polarization effect on a nano-rod array (fabricated by OAD) shows that the plasmon energy spectrum of a nano-rod red-shifts and broadens in visible range when strikes with p-polarized light, but it has a sharp peak in the UV wavelength range [62].…”
Section: Lspr Design Parameters Polarization Effectmentioning
confidence: 99%